The historical representation and near-future (2050) projections of the Coral Sea current system in CMIP6 HighResMIP - Jodie A. Schlaefer; Clothilde Langlais; Severine Choukroun; Mathieu Mongin; Mark E. Baird (Ocean Science, 2025)
The Coral Sea houses expansive coral reefs. Reef health is inextricably linked to water temperatures, which are regulated by the hydrodynamic environment. The ocean current system in the Coral Sea is dominated by jets of the South Equatorial Current (SEC): the North Vanuatu Jet (NVJ), the North Caledonian Jet (NCJ) and the South Caledonian Jet (SCJ). We investigated the projected near-future (2050) changes in the temperature and transport structure of the Coral Sea using the three highest-resolution climate models from the high-resolution coupled modelling experiment (HighResMIP) conducted within the latest iteration of the Coupled Model Intercomparison Project Phase 6 (CMIP6). We found that the HighResMIP models successfully represented the historical temperature and transport structure of the SEC jets and their El Niño–Southern Oscillation-related variability. Surface ocean warming of 0.78 and 1.12 °C was projected in the Coral Sea under 1.5 and 2 °C global air temperature warming, respectively. The maximum depth of the warming signal deepened by 30 m per decade, penetrating to 400 m by 2050. This indicated the additional thermal stress that could be experienced by Coral Sea ecosystems. Interestingly, the surface warming was associated with a sub-surface cooling between 400 and 600 m. Decreases in the transports of the NVJ and NCJ and an intensification of the SCJ were also projected in the HighResMIP models. The magnitudes of the changes were relatively small (2 % to 7 % of historical means) and of a similar order to the variability in transport associated with the El Niño–Southern Oscillation. Our analysis further showed that the transport projections of the NVJ and NCJ varied with depth, where surface intensifications coincided with the areas of greatest warming. These changes could modify western boundary currents and upwelling dynamics on the Great Barrier Reef shelf.

Impact of phytoplankton, CDOM, and suspended sediments on the vertical attenuation of light, changing heat content and circulation on a continental shelf: A modelling study of the Great Barrier Reef - Anna Maggiorano; Mark Baird; Clothilde Langlais; Mathieu Mongin; Jennifer Skerratt (Ocean Modelling, 2025)

The Development of a Floating Mono-Particle “Sun Shield” to Protect Corals from High Irradiance during Bleaching Conditions - Joel M. P. Scofield; Emma L. Prime; Florita Flores; Andrea Severati; Mathieu Mongin; Elodie Bougeot; Mark E. Baird; Andrew P. Negri; Greg G. Qiao (Journal of Marine Science and Engineering, 2024)
Coral bleaching is occurring more frequently as the climate changes, with multiple mass mortality events recently recorded on the Great Barrier Reef. Thermal stress coupled with high irradiance have previously been shown to be primary causes for coral bleaching. Therefore, a reduction in either of these pressures could reduce coral stress and eventual bleaching. Herein, we report the early development of a novel technology capable of reducing the amount of light entering a water body by ~20% in open ocean conditions. This mono-particle “sun shield” consists of an ultra-thin monolayer material and reflective calcium carbonate particles. The monolayer enables spreading of the particles into a thin film across the water surface, with only small amounts of material needed: 7.1 g/m2. A numerical modelling case study of residence times and the build-up of reactive oxygen stress in corals showed that the successful application of a stable film over the Lizard Island reef flat could reduce the reactive oxygen stress to below bleaching levels across approximately 1.5 km2 of reef area. With further development, mono-particle films such as this have the potential to be deployed over at-risk coral reefs at relatively small scales during predicted heatwave conditions, potentially reducing the severity of bleaching on coral reefs.

Dispersal of the pesticide diuron in the Great Barrier Reef - Jennifer Skerratt; Mark E. Baird; Mathieu Mongin; Robin Ellis; Rachael A. Smith; Melanie Shaw; Andy D.L. Steven (Science of The Total Environment, 2023)

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

Shifts in coralline algae, macroalgae, and coral juveniles in the Great Barrier Reef associated with present‐day ocean acidification - Joy N. Smith; Mathieu Mongin; Angus Thompson; Michelle J. Jonker; Glenn De'ath; Katharina E. Fabricius (Global Change Biology, 2020)
Seawater acidification from increasing CO 2 is often enhanced in coastal waters due to elevated nutrients and sedimentation. Our understanding of the effects of ocean and coastal acidification on present‐day ecosystems is limited. Here we use data from three independent large‐scale reef monitoring programs to assess coral reef responses associated with changes in mean aragonite saturation state (Ω ar ) in the Great Barrier Reef World Heritage Area (GBR). Spatial declines in mean Ω ar are associated with monotonic declines in crustose coralline algae (up to 3.1‐fold) and coral juvenile densities (1.3‐fold), while non‐calcifying macroalgae greatly increase (up to 3.2‐fold), additionally to their natural changes across and along the GBR. These three key groups of organisms are important proxies for coral reef health. Our data suggest a tipping point at Ω ar 3.5–3.6 for these coral reef health indicators. Suspended sediments acted as an additive stressor. The latter suggests that effective water quality management to reduce suspended sediments might locally and temporarily reduce the pressure from ocean acidification on these organisms.

Emulator-assisted data assimilation in complex models - Nugzar Yu Margvelashvili; Mike Herzfeld; Farhan Rizwi; Mathieu Mongin; Mark E. Baird; Emlyn Jones; Britta Schaffelke; Edward King; Thomas Schroeder (Ocean Dynamics, 2016)